Swedish Working Life Fund and the work to alter working life 1990-1995 - Swedish Working Life Fund (Swedish Working Life Fund, 1995)
During the period 1990-1995 approximately 25 000 workplace programmes were carried out with financial contribution from the Swedish Working Life Fund (ALF). The aim of the programmes was to develop labour organisations, to increase competence, to improve work environment, and to make rehabilitation attempts within working life. Within the framework of the evaluation project ´Arbetslivsfonden som förändringsprogram´ a questionnaire was distributed to 1 800 participating projects. The survey was carried out by Statistics Sweden by order of ALF. The sample was drawn from the project register of the Swedish Working Life Fund (winter 1993/1994). Projects closed before February 17 1993 were excluded, as well as projects started after March 31 1993. Only projects receiving 26 000 SEK or more were included. The questionnaire contained questions about the project work; contributors of vital initiatives; for how long time various persons and groups participated in the project work; ideas and activities discussed; time consumed distributed on various activities; contacts with the Swedish Working Life Fund; changes occurring after the start of the project, and if these changes depended on the project; achievements to rehabilitate long-term sicklisted; staff training; and activities occurring before the application for contribution from the fund. The data collection also include information on branch, number of men and women respectively at the workplace, contribution granted, and types of measures taken.

Under åren 1990 till 1995 genomfördes nära 25 000 program för utveckling av arbetsorganisation, kompetens, arbetsmiljö och rehabiliteringsansatser inom svenskt arbetsliv med stöd från Arbetslivsfonden (ALF). Inom ramen för utvärderingsprojektet 'Arbetslivsfonden som förändringsprogram' genomfördes en större enkätundersökning. Undersökningen utfördes av Statistiska Centralbyrån på uppdrag av fonden. Urvalet drogs ur ALF:s projektregister från vintern 1993/94. Projekt som avslutats före 17/2 1993 uteslöts liksom projekt påbörjade efter 31/3 1993. Endast projekt som erhållit minst 26000 kr medtogs. Enkäten innehöll frågor om projektarbetet; vem som bidragit med avgörande initiativ; hur lång tid olika personer och grupper deltagit i fondprojektet; idéer och aktiviteter som diskuterats; hur tiden fördelats på olika områden; kontakter med ALF; förändringar som inträffat sedan fondprojektet kom igång och om dessa beror på projektet; insatser för att få tillbaka långtidssjukskrivna till arbetslivet; personalutbildning; samt aktiviteter som förekom tiden innan fond¬medlen söktes. Studien innehåller även uppgifter om bransch, antal män respektive kvinnor på arbetsplatsen, beviljat bidrag, delbidrag samt åtgärdstyper
Arbetslivsfonden och arbetet med att förändra svenskt arbetsliv 1990-1995
Keywords: Health care services and policies; Hälso- och sjukvårdstjänster och -politik; Employment; Sysselsättning; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap